2019
DOI: 10.3389/fgene.2019.00481
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Behavioral Outcomes After Childhood TBI: A Novel Systems Biology-Informed Approach

Abstract: Objectives: To test whether genetic associations with behavioral outcomes after early childhood traumatic brain injury (TBI) are enriched for biologic pathways underpinning neurocognitive and behavioral networks. Design: Cross-sectional evaluation of the association of genetic factors with early (~ 6 months) and long-term (~ 7 years) post-TBI behavioral outcomes. We combined systems biology and genetic association testing methodologies to identify biologic pathways associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Recovery from TBI represents a very complex phenotype. A limitation of much work to date has been a reliance on candidate gene studies with limited numbers of patients, some of which have not proven reproducible 10 , 11 . The Genetics Association in Neurotrauma (GAIN) Consortium ( https://intbir.nih.gov/node/45 ) will produce the first GWAS to study biological mechanisms that modulate response and recovery after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery from TBI represents a very complex phenotype. A limitation of much work to date has been a reliance on candidate gene studies with limited numbers of patients, some of which have not proven reproducible 10 , 11 . The Genetics Association in Neurotrauma (GAIN) Consortium ( https://intbir.nih.gov/node/45 ) will produce the first GWAS to study biological mechanisms that modulate response and recovery after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Scarcity of available genomic datasets for our phenotype of interest, namely, CPSP, makes GWAS daunting. Systems-biology approaches have been used successfully for identifying gene pathways implicated in other phenotypes ( Kurowski et al, 2012 ; Jegga, 2014 ; Kurowski et al, 2019 ) as they allow leveraging known genomic data sources to prioritize functional genes for association, thereby decreasing the statistical burden. In our study, literature derived training sets showed enrichment for CPSP, with genes previously known to play an important role in pain.…”
Section: Discussionmentioning
confidence: 99%
“…Case gene variants were analyzed as sequence of cumulative sums of ranked variant sets with 10% increment, as has been done in a prior study ( Kurowski et al, 2019 ). The first addend in each sequence was the training gene variant set.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to age at injury and injury severity, the pathological consequence of TBI can be influenced by a variety of genetic factors ( Wilson and Montgomery, 2007 ; Dardiotis et al, 2010 ; Bennett et al, 2016 ; Kurowski et al, 2019 ). As it relates to TBI-induced AD, polymorphisms in Apolipoprotein E (APOE) appear to be the most prominent risk-modifying genetic factor.…”
Section: Future Directions: Role Of Sex and Genetic Factorsmentioning
confidence: 99%